Prime Minister Decree No. 3944 Of The Year 2025 - Prime Minister (The Middle East Library For Economic Services, 2025)
Prime Minister Decree No. 3944 Of The Year 2025 Saturday, corresponding to the 1st of November 2025 (AD), shall be deemed an official paid holiday for the workers in the ministries, governmental departments, public authorities, local administrative units, companies of the public sector, public business sector and private sector, on the occasion of the Opening of the Grand Egyptian Museum.